CURRENT TREATMENT OPTIONS FOR CHILDREN AND ADOLESCENTS LIVING WITH HUMAN IMMUNODEFICIENCY VIRUS INFECTION: PEDIATRIC HIV TREATMENT - Popovic Dragonjic, Lidija; Ranković , Aleksandar; Cvetanović, Maja; Ćosić Petković, Milica; Spasić, Jelena; Tomić, Jovana; Krtinić, Dane (Acta medicae Medianae, 2026)
The goal of human immunodeficiency virus (HIV) infection treatment in both adults and children and adolescents is to achieve a stable virological response, i.e., undetectable viral load in the blood for more than six months and recovery of immunity. Antiretroviral treatment of children and adolescents living with HIV (C/ALHIV) is even more specific and more difficult due to poorer therapeutic adherence, longer duration of infection and consequent toxic effects as well as chronic microinflammation. Another complicating factor is the lack of adequate pediatric pharmaceutical co-formulations depending on the region. With progress and the emergence of innovative types of therapy and strict guidelines, C/ALHIV are improving their quality of life and immune status. The most used official guidelines are the recommendations of the European AIDS Clinical Society (EACS), the World Health Organization (WHO), and the Center for Disease Control and Prevention (CDC). According to them, along with local conditions and opportunities, national guidelines are formed at the level of individual countries.